2017
DOI: 10.1111/nyas.13391
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐specific diversity in the expression and organization of cytoplasmic plaque proteins of apical junctions

Abstract: Tight and adherens junctions play critical roles in the barrier, adhesion, and signaling functions of epithelial and endothelial cells. How the molecular organization of these junctions is tuned to the widely diverse physiological requirements of each tissue type is not well understood. Here, we address this question by examining the expression, localization, and interactions of major cytoplasmic plaque proteins of tight and adherens junctions in different cultured epithelial and endothelial cell lines. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 115 publications
0
35
0
Order By: Relevance
“…The Junctional Clustering of ADAM10 Correlates with Its Maturation, Cell Confluency, and a-Toxin-Dependent Cell Death Using an antibody validated on cells depleted of ADAM10 (Figures S1A-S1D), we examined ADAM10 immunofluorescence (IF) localization in confluent kidney (mouse cortical collecting duct, mCCD]) cells, grown on Transwell filters to enhance apico-basal polarization. ADAM10 was co-localized with PLEKHA7 at apical junctions (arrows, Figures 1A and 1B), which comprise the zonular junctions TJ and ZA, and where the respective markers ZO-1 and PLEKHA7 show partially overlapped localizations (Pulimeno et al, 2010;Vasileva et al, 2017). It should be noted that ZA proteins and some TJ proteins, including ZO-1 (Howarth et al, 1992), are localized at AJs in non-epithelial cells, such as myeloblastic-derived Hap1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The Junctional Clustering of ADAM10 Correlates with Its Maturation, Cell Confluency, and a-Toxin-Dependent Cell Death Using an antibody validated on cells depleted of ADAM10 (Figures S1A-S1D), we examined ADAM10 immunofluorescence (IF) localization in confluent kidney (mouse cortical collecting duct, mCCD]) cells, grown on Transwell filters to enhance apico-basal polarization. ADAM10 was co-localized with PLEKHA7 at apical junctions (arrows, Figures 1A and 1B), which comprise the zonular junctions TJ and ZA, and where the respective markers ZO-1 and PLEKHA7 show partially overlapped localizations (Pulimeno et al, 2010;Vasileva et al, 2017). It should be noted that ZA proteins and some TJ proteins, including ZO-1 (Howarth et al, 1992), are localized at AJs in non-epithelial cells, such as myeloblastic-derived Hap1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…IB analysis showed distinct patterns of expression for each WW-PLEKHA in epithelial and non-epithelial cell lines (Fig. S3A and (Vasileva et al, 2017)). For IF analysis of endogenous proteins, we used epithelial cells from the collecting duct (mCCD) and the proximal tubule (MDCK) of the kidney, grown to full polarization either on Transwell filters or as cysts in Matrigel, and myeloblastic-derived Hap1 cells (Shah et al, 2018).…”
Section: Plekha5 Plekha6 and Plekha7 Show Distinct Localizations In Cells And Tissues And Define Cytoplasmic And Microtubule-associated Lmentioning
confidence: 99%
“…Culture conditions for mouse cortical collecting duct cells (mCCD), Madin-Darby canine kidney cells (MDCKII Tet-off), mouse brain microvascular endothelial (endothelioma) cell line (bEnd.3), mouse heart endothelial cell line (H5V), human lung carcinoma cell line (A427), ciliated aortic mouse embryonic endothelial cells (meEC), human keratinocyte cell line (HaCaT) (Vasileva et al, 2017), human umbilical vascular endothelial cells (HUVEC) (Rouaud et al, 2019), haploid human cells (Hap1) (Popov et al, 2015), mouse mammary epithelial cells (Eph4), human intestinal carcinoma cells (Caco-2) (Spadaro et al, 2017), human embryonic kidney epithelial cells (HEK293T) (Rouaud et al, 2020) were described previously.…”
Section: Cell Culturementioning
confidence: 99%
“…Current research reports that the interaction of PDZD11 with PLEKHA7 is significantly associated with tight and adherens junctions (Guerrera et al, 2016;Vasileva et al, 2017). However, to the best of our knowledge, no study has investigated the role of PDZD11 in liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also shown that cooperative binding of the tandem WW domains (e.g., WW1 and WW2) of PLEKHA7 to PDZD11 promoted the binding of the C-terminus of Tspan33 to PLEKHA7. Furthermore, the complex formation of PLEKHA7, PDZD11, ADAM10 and its molecular chaperone Tspan33 through promoting the junctional clustering of the α-toxin receptor ADAM10 makes cells more sensitive to the cytotoxic effects of Staphylococcus aureus α-toxin (Vasileva et al, 2017;Rouaud et al, 2020).…”
Section: Introductionmentioning
confidence: 99%